ANALISIS STRUKTUR DAN AMANAT TEKS GEGURITAN NYEPI - Mas Wahami Suci, Luh (Humanis; Volume 11. No2. Mei 2015)
This study, entitled "Analysis of the Structure and Mandate Text Geguritan Nyepi". The purpose of this study was to describe the structure and mandate contained in the text Geguritan Nyepi. Text Geguritan Nyepi analyzed using structural theory. The methods and techniques used consist of several stages, namely: (1) the stage of providing data that is read using the reading is done repeatedly to be able to better understand the content of the manuscript Geguritan Nyepi, assisted with literal and idiomatic translation techniques, (2) the stage of data analysis, using qualitative methods, aided by descriptive techniques analytic, and (3) the stage presentation of the results of data analysis using formal and informal methods, aided by inductive deduktif- thought patterns. The results of this intensive search is unfolding Nyepi Geguritan structure includes formal structure and narrative structure. Formal structure includes: a code language and literature, style, and variety of language, while the narrative structure include: incident, plot, character and characterization, setting, theme, and the mandate. Analysis of the mandate contained in the mandate of the Geguritan Nyepi chess initiation ceremonies and retreats, the mandate of the ethics and mandate of the development of literature and culture.
Keywords: Geguritan, Structure and Mandate